Perilaku Memilih Rasional dalam Pemilu Indonesia Kontemporer: Perbandingan Pemilu 2014 dan Pemilu 2019 - Wasisto Raharjo Jati (Badan Pengawas Pemilihan Umum, 2022)
The rational voting behaviour within current Indonesian political situation is still debatable. It basically shows the different socio-economic and socio-political backgrounds among the voters that results in different voting behaviour expressions. The urban voters whom middle-class background seems to be rational voters. They would like to be open-minded accepting various preferences rather than one or two preferences. This makes the urban voters could critically asses the parties and candidates they preferred with. Most importantly, they would stress some important issues like money poltiics and national economic evaluation to address voting behaviour expressions. For some reasons, these two factors still be important issues in shaping political choices in Indonesia. This paper will further elaborate empirically the rational voting behaviour in Indonesia. Specifically, this paper used the survey data from 2014 and 2019 elections to elaborate rational voting behaviour recently. These two recent elections basically could represent the latest voting behaviour expressions in Indonesia.